Amphoteric cyclodextrin-based dual-ligand metal organic framework separation membrane and preparation method thereof
Through the preparation method of the amphoteric cyclodextrin biligand metal organic frame separation membrane, the existing nanofiltration membrane has solved the problems of low water permeability and poor separation selectivity in heavy metal ion separation, and achieved efficient heavy metal ion separation and water treatment effects.
Patent Information
- Application Number
- CN202211485311.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-11-24
AI Technical Summary
When separating heavy metal ions of similar sizes, existing nanofiltration membranes have problems such as low water permeability and poor separation selectivity, which is difficult to meet the needs of complex water treatment.
The preparation method of the amphoteric cyclodextrin biligand metal organic frame separation membrane is adopted, and the epoxy cross-linking of zwitterionic amine monomer and cyclodextrin in an alkaline aqueous solution is carried out to form an amphoteric cyclodextrin material, and the membrane is grown in situ on the surface of the porous support membrane.
It achieves high water permeability and excellent selectivity for separation of heavy metal ions, and is suitable for the treatment of heavy metal wastewater and the recycling of resource substances.
Smart Images

Figure CN115715940B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water treatment membrane separation, and in particular relates to a preparation method of a separation membrane based on an amphiphilic cyclodextrin double ligand metal organic framework. Background Art
[0002] Since aqueous solutions containing heavy metal ions have complex compositions, they usually contain multiple heavy metal ions with similar ionic radii and similar chemical properties, making separation extremely difficult (Chem. Eng. J., 2021, 417: 127930; J. Membr. Sci., 2002, 210 (1): 137–145; Sep. Purif. Technol., 2010, 75 (1): 8-14.). Membrane separation has rapidly developed into a modern new and efficient water treatment separation technology with its advantages of low energy consumption, high efficiency, no secondary pollution and continuous operation. Among them, pressure-driven nanofiltration membrane separation technology, with a membrane pore size range of 0.5-2nm, can be used to separate organic molecules with a molecular weight between 200-1000Da and inorganic salt ions of different valence states. Nanofiltration has the characteristics of high separation accuracy, large permeation flux, low operating pressure and low energy consumption, and has good application prospects in water treatment, heavy metal ion separation and resource material recovery (Mater. Today, 2021, 50: 516-532; Chem. Soc. Rev., 2017, 46: 7124-7144.). In order to meet the requirements of increasingly complex practical application separation systems, it is necessary to further develop nanofiltration membranes that have both high water permeability and heavy metal ion separation selectivity.
[0003] At present, nanofiltration membranes are mainly made of polymer materials such as cellulose, chitosan derivatives, polyvinyl alcohol and polyamide. However, the above-mentioned traditional polymer membrane structures are usually dense, with low water permeation flux and poor separation selectivity for different heavy metal ions (Coordin. Chem. Rev., 2022, 425: 213481). In recent years, with the rapid development of bionic nanochannel materials, such as carbon nanotubes, modified graphene materials, zeolite molecular sieves, metal organic framework materials and covalent organic framework materials, they have gradually been used in the preparation of new nanofiltration membranes (ZL202011008514.3; Sep. Purif. Technol., 2021, 269: 118719; Science, 2017, 356: 1137). The pore structure of the nanomaterial itself gives the nanofiltration membrane more mass transfer channels, promoting the efficient transfer of substances through the membrane. However, most of the separation membranes based on nanomaterials have large pore sizes, making it difficult to achieve accurate separation of heavy metal ions. Therefore, the development of nanofiltration membranes with ion recognition channel structures that can be used for heavy metal ion separation plays an important role in the treatment of heavy metal wastewater and the effective recovery of resource substances.
[0004] Cyclodextrin, as a non-toxic material with low preparation cost and unique cavity structure, has gradually been used in the preparation of separation membranes. Studies have found that the hydrophobic cavity diameter of cyclodextrin is 0.57-0.95 angstroms, which can allow water to pass through. At the same time, the special interaction between cyclodextrin and metal ions can achieve the separation of metal ions (J. Mater. Chem. A, 2019, 7: 2055; Polymers 2019, 11: 1737). However, cyclodextrin itself has poor solubility and low reactivity, making it difficult to prepare membranes by simple methods. As a new type of polymer material, zwitterionic polymers contain both anionic and cationic groups in their molecular chains, have strong hydrophilicity and anti-fouling properties, and have gradually attracted the research interest of membrane scientists at home and abroad. Metal-organic framework materials refer to metal-organic framework materials with periodic porous network structures formed by self-assembly of organic ligands and metal ions / clusters (Chem. Soc. Rev., 2019, 48(14): 3811-3841). They have the characteristics of high porosity, adjustable pore size, and clear pore structure, which are very important for the preparation of separation membranes with efficient recognition and selective nanochannel structures. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a separation membrane based on amphoteric cyclodextrin dual ligand metal organic framework and a preparation method thereof. The present invention uses amphoteric ion amine monomer and cyclodextrin as raw materials, and treats them with an epoxy crosslinking agent to prepare amphoteric cyclodextrin materials in an alkaline aqueous solution. Amphoteric cyclodextrin contains both anionic and cationic functional groups, which have strong hydrophilicity and coordination with metal ions, which is conducive to promoting the in-situ growth construction of amphoteric cyclodextrin dual ligand metal organic framework separation membrane, while improving the membrane water permeability and structural stability. Then, amphoteric cyclodextrin is used as a functional organic ligand to carry out in-situ growth construction of amphoteric cyclodextrin dual ligand metal organic framework separation membrane on the surface of a porous support membrane. The separation membrane constructed by the above strategy, the hydrophobic cavity of the amphoteric cyclodextrin itself and the pore structure of the metal organic framework can promote the high-speed transmission of water molecules through the membrane, and at the same time have special recognition selectivity for heavy metal ions. In addition, the raw materials used in the present invention are commercially available reagents with low cost, the membrane preparation method is simple and easy to operate, and the obtained membrane has high water permeability, excellent heavy metal ion separation selectivity and stability, and therefore has good industrial application prospects.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A method for preparing a separation membrane based on an amphiphilic cyclodextrin dual ligand metal organic framework comprises the following steps:
[0008] 1) dissolving 1.0 to 7.0 parts by weight of cyclodextrin, 2.5 to 12 parts by weight of zwitterionic amine monomers and 0.3 to 1.5 parts by weight of epoxy crosslinking agents in 100 parts by weight of alkaline aqueous solution, reacting at 50 to 70° C. for 1 to 4 hours, and after the reaction, purifying the product by dissolving and precipitating, and then heating and drying to obtain amphoteric cyclodextrin solid powder;
[0009] 2) adding 0.1 to 0.5 parts by weight of the above-mentioned amphoteric cyclodextrin solid powder and 0.2 to 2 parts by weight of a metal acid salt to 100 parts by weight of a mixed solvent of water and ethanol to obtain a mixed solution, coating the above-mentioned mixed solution on the surface of a porous support membrane, depositing amphoteric cyclodextrin metal coordination crystals on the surface of the porous support membrane, and then impregnating with a second organic ligand solution with a mass percentage concentration of 0.1 to 1.0 wt% to form a primary ecological membrane based on an amphoteric cyclodextrin dual ligand metal organic framework;
[0010] 3) Immersing the above-mentioned amphiphilic cyclodextrin dual ligand metal organic framework based primary ecological membrane in a cross-linking agent solution with a mass percentage concentration of 0.05-0.3wt% for cross-linking, and finally subjecting it to thermal curing treatment and washing with deionized water to obtain an amphiphilic cyclodextrin dual ligand metal organic framework membrane;
[0011] The cyclodextrin in step 1) is one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin mixed in any proportion; the zwitterionic amine monomer in step 1) is N-aminoethyl piperazine propane sulfonate, 2,6-diaminopyridine propane sulfonate, 2,6-diaminopyridine propane carboxylate, 1,2-bis[N-methyl-N-(3-sulfopropyl)-alkylammonium]ethane, 1,4-butanediol bisulfosuccinate hydroxypropropylquaternary ammonium diester sodium sulfonate. diester) are mixed in any proportion; the epoxy crosslinking agent described in step 1) is one or more of epichlorohydrin, di(2-epoxypropyl) ether, ethylene glycol diglycidyl ether, and trimethylolpropane triglycidyl ether are mixed in any proportion; the metal acid salt described in step 2) is one or more of zinc acetate, zinc nitrate, ferric chloride, and cobalt nitrate are mixed in any proportion; the porous support membrane described in step 2) is a polysulfone ultrafiltration membrane, a polyethersulfone ultrafiltration membrane, a polyacrylonitrile ultrafiltration membrane, or a polyvinylidene fluoride ultrafiltration membrane; the second organic ligand described in step 2) is one or more of benzimidazole, 2-methylimidazole, and trimesic acid are mixed in any proportion; the crosslinking agent described in step 3) is one or more of phthaloyl chloride, terephthaloyl chloride, trimesic chloride, trimesic acid, terephthalaldehyde, trialdehyde phloroglucinol, cyanuric chloride, and hexachlorotripolyphosphazene are mixed in any proportion.
[0012] Preferably, the alkaline aqueous solution described in step 1) is a sodium hydroxide or potassium hydroxide aqueous solution with a mass percentage concentration of 0.01 to 1.0 wt%; the dissolution precipitation purification method described in step 1) is to dissolve the product in water and precipitate it in methanol, and obtain a purified product after 3 to 6 dissolution precipitations; the heating and drying conditions described in step 1) are vacuum drying at 40 to 60° C. for 3 to 12 hours; the mass ratio of water to ethanol in the mixed solution described in step 2) is 5:1 to 5:4; the coating conditions of the mixed solution described in step 2) are to coat 0.5 to 10% at 15 to 25° C. 3 hours, so that the mixed solution is evenly distributed on the porous support membrane; the solvent of the second organic ligand solution described in step 2) is water, methanol or ethanol; the immersion treatment condition of the second organic ligand solution described in step 2) is immersion at 15-25°C for 0.5-4 hours; the solvent of the crosslinker solution described in step 3) is n-hexane, cyclohexane, heptane or toluene, mesitylene; the crosslinking condition in the crosslinker solution described in step 3) is crosslinking at 15-25°C for 2-10 minutes; the thermal curing treatment condition described in step 3) is curing at 40-65°C for 10-30 minutes.
[0013] A separation membrane based on amphoteric cyclodextrin biligand metal organic framework prepared by the above preparation method can be used in the fields of separation of heavy metal ions of similar sizes and wastewater treatment and recycling.
[0014] Furthermore, heavy metal ions include Fe 2+ , Fe 3+ Cr 3+ , Cu 2+ wait.
[0015] The present invention discloses a metal organic framework separation membrane based on amphiphilic cyclodextrin dual ligand for Fe 3+ Has excellent selectivity.
[0016] The dual-ligand metal organic framework separation membrane constructed with amphoteric cyclodextrin in the present invention is firstly prepared in an alkaline aqueous solution using amphoteric ion amine monomer and cyclodextrin as raw materials, treated with an epoxy crosslinking agent, and then used as a functional organic ligand to in-situ grow on the surface of a porous support membrane to construct a dual-ligand metal organic framework separation membrane based on amphoteric cyclodextrin. The membrane has a water flux of 90 to 120 L·m at an operating pressure of 0.1 MPa. -2 ·h -1, the interception rate of ferric chloride metal salt solution is higher than 95%, and the heavy metal salt separation selectivity is 14-25. The hydrophobic cavity of the amphoteric cyclodextrin itself and the metal organic framework pore structure in the present invention can promote the high-speed transmission of water molecules through the membrane, and at the same time have special recognition selectivity for heavy metal ions. In addition, the membrane preparation method selected by the present invention is simple and easy to operate, and the obtained membrane has high water permeability, excellent heavy metal ion separation selectivity and stability, so it has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a surface morphology image of the amphoteric cyclodextrin dual ligand metal organic framework separation membrane described in Example 3 of the present invention. DETAILED DESCRIPTION
[0018] The present invention provides a separation membrane based on an amphiphilic cyclodextrin dual ligand metal organic framework and a preparation method thereof. Specifically, the preparation method comprises the following steps:
[0019] 1) dissolving 1.0 to 7.0 parts by weight of cyclodextrin, 2.5 to 12 parts by weight of zwitterionic amine monomers and 0.3 to 1.5 parts by weight of epoxy crosslinking agents in 100 parts by weight of alkaline aqueous solution, reacting at 50 to 70° C. for 1 to 4 hours, and after the reaction, purifying the product by dissolving and precipitating, and then heating and drying to obtain amphoteric cyclodextrin solid powder;
[0020] 2) adding 0.1 to 0.5 parts by weight of the above-mentioned amphoteric cyclodextrin solid powder and 0.2 to 2 parts by weight of a metal acid salt to 100 parts by weight of a mixed solvent of water and ethanol to obtain a mixed solution, coating the above-mentioned mixed solution on the surface of a porous support membrane, depositing amphoteric cyclodextrin metal coordination crystals on the surface of the porous support membrane, and then impregnating with a second organic ligand solution with a mass percentage concentration of 0.1 to 1.0 wt% to form a primary ecological membrane based on an amphoteric cyclodextrin dual ligand metal organic framework;
[0021] 3) Immersing the above-mentioned amphiphilic cyclodextrin dual ligand metal organic framework based primary ecological membrane in a cross-linking agent solution with a mass percentage concentration of 0.05-0.3wt% for cross-linking, and finally subjecting it to thermal curing treatment and washing with deionized water to obtain an amphiphilic cyclodextrin dual ligand metal organic framework membrane;
[0022] The cyclodextrin described in step 1) is composed of one or more of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin mixed in any proportion; the zwitterionic amine monomer described in step 1) is composed of one or more of N-aminoethylpiperazine propane-1-sulfonic acid inner salt, 2,6-diaminopyridine propane-1-sulfonic acid inner salt, 2,6-diaminopyridine propane-1-carboxylic acid inner salt, 1,2-bis[N-methyl-N-(3-sulfopropyl)-alkylammonium]ethane, and butanediol disuccinic acid dichlorohydroxypropyl quaternary ammonium diester sodium sulfonate mixed in any proportion; the epoxy crosslinking agent described in step 1) is one or more of epichlorohydrin, di(2-epoxypropyl) ether, ethylene glycol diglycidyl ether, and trimethylolpropane triglycidyl ether. One or more are mixed in any proportion; the metal acid salt described in step 2) is one or more of zinc acetate, zinc nitrate, ferric chloride, and cobalt nitrate mixed in any proportion; the porous support membrane described in step 2) is a polysulfone ultrafiltration membrane, a polyethersulfone ultrafiltration membrane, a polyacrylonitrile ultrafiltration membrane, or a polyvinylidene fluoride ultrafiltration membrane; the second organic ligand described in step 2) is one or more of benzimidazole, 2-methylimidazole, and trimesic acid mixed in any proportion; the cross-linking agent described in step 3) is one or more of phthaloyl chloride, terephthaloyl chloride, trimesic chloride, trimesic acid, terephthalaldehyde, trialdehyde phloroglucinol, cyanuric chloride, and hexachlorotriphosphazene mixed in any proportion.
[0023] The alkaline aqueous solution described in step 1) is a sodium hydroxide or potassium hydroxide aqueous solution with a mass percentage concentration of 0.01 to 1.0 wt%; the dissolution precipitation purification method described in step 1) is to dissolve the product in water and precipitate it in methanol, and obtain a purified product after 3 to 6 dissolution precipitations; the heating and drying conditions described in step 1) are vacuum drying at 40 to 60° C. for 3 to 12 hours; the mass ratio of water to ethanol in the mixed solvent described in step 2) is 5:1 to 5:4; the coating conditions of the mixed solution described in step 2) are at 15 to 25° C. The coating is carried out for 0.5 to 3 hours; the solvent of the second organic ligand solution described in step 2) is water, methanol or ethanol; the immersion treatment condition of the second organic ligand solution described in step 2) is immersion at 15 to 25°C for 0.5 to 4 hours; the solvent of the crosslinking agent solution described in step 3) is n-hexane, cyclohexane, heptane, toluene or mesitylene; the crosslinking condition in the crosslinking agent solution described in step 3) is crosslinking at 15 to 25°C for 2 to 10 minutes; the heat curing treatment condition described in step 3) is curing at 40 to 65°C for 10 to 30 minutes.
[0024] Embodiments of the present invention are given below, but the present invention is not limited by the embodiments;
[0025] In the following embodiments, the separation performance test method of the amphiphilic cyclodextrin dual ligand metal organic framework separation membrane is as follows: the separation membrane is placed in a conventional pressure-driven membrane test device in the art, and the membrane is pre-pressed at an operating pressure of 0.1 MPa for 1 h before the test, and then the water permeation flux (J) and the retention rate (R) of the membrane are measured under the test conditions of 25°C and 0.1 MPa, and the calculation formula is: J = V / (At); R = 1-C p / C f ; Where V is the volume of the liquid passing through the membrane, and A is the effective area of the membrane, which is 19.6 cm 2 , t - running time, C p - Permeate concentration, C f - Feed solution concentration; The concentration of heavy metal salt solution is obtained by measuring the ultraviolet absorbance value and conductivity of the solution. In addition, the calculation formula for the separation selectivity of heavy metal ions is: S = 1-(R 2 / R 1 ), where R 1 is the retention rate of ferric chloride, R 2 is the retention rate of other types of heavy metal salts.
[0026] Embodiment 1:
[0027] 1.0 g of β-cyclodextrin, 2.5 g of N-aminoethylpiperazine propane-1-sulfonic acid inner salt and 0.3 g of epichlorohydrin were dissolved in 100 g of 0.01 wt% sodium hydroxide aqueous solution, and reacted at 70° C. for 1 hour. After the reaction, the product was dissolved in water and purified by methanol precipitation 3 times, and vacuum dried at 40° C. for 12 hours to obtain amphoteric cyclodextrin solid powder;
[0028] Take 0.1g of amphoteric β-cyclodextrin solid powder and 0.2g of zinc acetate, add 100g of a mixed solvent of water and ethanol in a mass ratio of 5:1 to obtain a mixed solution, apply the above mixed solution on the surface of a polysulfone ultrafiltration membrane at 15°C for 0.5 hours, and deposit amphoteric β-cyclodextrin metal coordination crystals on the surface of the polysulfone ultrafiltration membrane. Then, immerse it in 0.1wt% benzimidazole ethanol solution at 15°C for 0.5 hours to form an amphoteric cyclodextrin biligand metal organic framework primary eco-membrane, and then immerse the above amphoteric cyclodextrin biligand metal organic framework primary eco-membrane in 0.05wt% trimesoyl chloride n-hexane solution, cross-link at 15°C for 10 minutes, and finally cure at 40°C for 30 minutes. After washing with deionized water, a separation membrane based on amphoteric cyclodextrin biligand metal organic framework is obtained.
[0029] The amphiphilic cyclodextrin dual ligand metal organic framework separation membrane has a good performance at 25℃ and 0.1MPa pressure for 1g·L -1 The filtration separation effect of heavy metal salt solution is: water flux is 90.0L·m -2 ·h -1The retention rates of ferric chloride, chromic chloride, ferrous chloride and cupric chloride were 95.2%, 31.2%, 23.7% and 25.5%, respectively. The separation selectivities of ferric chloride / chromic chloride, ferric chloride / ferrous chloride and ferric chloride / cupric chloride were 14.3, 15.9 and 15.5, respectively.
[0030] Embodiment 2:
[0031] 7.0 g of β-cyclodextrin, 12 g of N-aminoethylpiperazine propane-1-sulfonic acid inner salt and 1.5 g of epichlorohydrin were dissolved in 100 g of 0.1 wt% sodium hydroxide aqueous solution, and reacted at 50° C. for 4 hours. After the reaction, the product was dissolved in water and purified by methanol precipitation 6 times, and vacuum dried at 60° C. for 3 hours to obtain amphoteric cyclodextrin solid powder;
[0032] Take 0.5g of amphoteric β-cyclodextrin solid powder and 2g of zinc acetate, add 100g of a mixed solvent of water and ethanol in a mass ratio of 5:4 to obtain a mixed solution, and coat the above mixed solution on the surface of a polysulfone ultrafiltration membrane at 25°C for 3 hours, and the amphoteric β-cyclodextrin metal coordination crystals are deposited on the surface of the polysulfone ultrafiltration membrane. Then, it is immersed in 1.0wt% benzimidazole ethanol solution at 25°C for 4 hours to form an amphoteric cyclodextrin biligand metal organic framework primary eco-membrane, and then the above amphoteric cyclodextrin biligand metal organic framework primary eco-membrane is immersed in 0.3wt% benzyl chloride n-hexane solution, cross-linked at 25°C for 2 minutes, and finally cured at 65°C for 10 minutes. After washing with deionized water, a separation membrane based on amphoteric cyclodextrin biligand metal organic framework is obtained.
[0033] The amphiphilic cyclodextrin dual ligand metal organic framework separation membrane has a good performance at 25℃ and 0.1MPa pressure for 1g·L -1 The filtration separation effect of heavy metal salt solution is: water flux is 120.0L·m -2 ·h -1 The retention rates of ferric chloride, chromic chloride, ferrous chloride and cupric chloride were 95.8%, 27.2%, 21.6% and 23.5%, respectively. The separation selectivities of ferric chloride / chromic chloride, ferric chloride / ferrous chloride and ferric chloride / cupric chloride were 17.3, 18.7 and 18.2, respectively.
[0034] Embodiment 3:
[0035] 4.0 g of β-cyclodextrin, 10 g of N-aminoethylpiperazine propane-1-sulfonic acid inner salt and 0.9 g of epichlorohydrin were dissolved in 100 g of 0.05 wt% sodium hydroxide aqueous solution, and reacted at 60° C. for 2 hours. After the reaction, the product was purified by water dissolution and methanol precipitation three times, and vacuum dried at 40° C. for 12 hours to obtain amphoteric cyclodextrin solid powder;
[0036] Take 0.3g of amphoteric β-cyclodextrin solid powder and 1g of zinc acetate, add 100g of a mixed solvent of water and ethanol in a mass ratio of 5:2 to obtain a mixed solution, apply the above mixed solution on the surface of a polysulfone ultrafiltration membrane at 20°C for 1 hour, and deposit amphoteric β-cyclodextrin metal coordination crystals on the surface of the polysulfone ultrafiltration membrane. Then, immerse it in 0.3wt% benzimidazole ethanol solution at 20°C for 1 hour to form an amphoteric cyclodextrin biligand metal organic framework primary eco-membrane, and then immerse the above amphoteric cyclodextrin biligand metal organic framework primary eco-membrane in 0.2wt% benzyl chloride n-hexane solution, cross-link at 20°C for 5 minutes, and finally cure at 60°C for 15 minutes. After washing with deionized water, a separation membrane based on amphoteric cyclodextrin biligand metal organic framework is obtained.
[0037] The amphiphilic cyclodextrin dual ligand metal organic framework separation membrane has a good performance at 25℃ and 0.1MPa pressure for 1g·L -1 The filtration separation effect of heavy metal salt solution is: water flux is 105.0L·m -2 ·h -1 The retention rates of ferric chloride, chromic chloride, ferrous chloride and cupric chloride were 96.5%, 22.3%, 14.3% and 16.7%, respectively. The separation selectivities of ferric chloride / chromic chloride, ferric chloride / ferrous chloride and ferric chloride / cupric chloride were 22.2, 24.5 and 23.8, respectively.
[0038] Comparative Example 1
[0039] Take 0.3g of the amphoteric β-cyclodextrin solid powder prepared in Example 3, add 100g of a mixed solution of water and ethanol in a mass ratio of 5:2 to obtain a mixed solution, and apply the mixed solution on the surface of a polysulfone ultrafiltration membrane at 20°C for 1 hour. The amphoteric β-cyclodextrin is deposited on the surface of the polysulfone ultrafiltration membrane to form an amphoteric cyclodextrin primary eco-membrane. The amphoteric cyclodextrin primary eco-membrane is then immersed in a 0.2wt% trimesoyl chloride n-hexane solution, cross-linked at 20°C for 5 minutes, and finally cured at 60°C for 15 minutes. After washing with deionized water, an amphoteric cyclodextrin separation membrane is obtained.
[0040] Comparative Example 2
[0041] Take 0.3g of the amphoteric β-cyclodextrin solid powder prepared in Example 3 and 1g of zinc acetate, add 100g of a mixed solution of water and ethanol in a mass ratio of 5:2 to obtain a mixed solution, and apply the above mixed solution on the surface of a polysulfone ultrafiltration membrane at 20°C for 1 hour. The amphoteric β-cyclodextrin metal coordination crystals are deposited on the surface of the polysulfone ultrafiltration membrane to form an amphoteric cyclodextrin metal coordination polymer primary ecological membrane. Then, the above amphoteric cyclodextrin metal coordination polymer primary ecological membrane is immersed in a 0.2wt% trimesoyl chloride n-hexane solution, cross-linked at 20°C for 5 minutes, and finally cured at 60°C for 15 minutes. After washing with deionized water, an amphoteric cyclodextrin metal coordination polymer separation membrane is obtained.
[0042] Comparative Example 3
[0043] Take 0.3g of anhydrous piperazine solid powder, add 100g of a mixed solution of water and ethanol in a mass ratio of 5:2 to obtain a mixed solution, apply the mixed solution on the surface of a polysulfone ultrafiltration membrane at 20°C for 1 hour, and the piperazine monomer is deposited on the surface of the polysulfone ultrafiltration membrane to form a piperazine primary eco membrane, then immerse the piperazine primary eco membrane in a 0.2wt% n-hexane solution of trimesoyl chloride, cross-link at 20°C for 5 minutes, and finally cure at 60°C for 15 minutes. After washing with deionized water, a polyamide separation membrane is obtained.
[0044] Table 1 Comparison of separation performance of different types of membranes prepared in Example 3 and Comparative Examples 1-3
[0045]
[0046] The results in Table 1 show that separation membranes can be prepared using all three methods, but their retention rates and water fluxes for metal salt solutions are quite different. This is because the methods used to prepare the membranes, the chemical composition and the physical structure of the membranes are all different.
[0047] In Comparative Example 1, amphiphilic cyclodextrin and polyacyl chloride molecules are used as membrane-forming materials, and the amphiphilic cyclodextrin membrane obtained by interfacial polymerization is cross-linked by polymer chains, with a dense membrane structure and low water flux; in Comparative Example 2, an amphiphilic cyclodextrin metal coordination polymer membrane is prepared using amphiphilic cyclodextrin, a coordinated metal solution and polyacyl chloride as membrane-forming materials. The membrane lacks a high-efficiency selective transmission channel structure, and the water flux and heavy metal separation selectivity are still not significantly improved; Comparative Example 3 is a traditional polyamide polymer membrane with a dense membrane structure. No nanochannel structure and recognition sites of amphiphilic cyclodextrin are introduced into the membrane, so the separation of different heavy metal ions cannot be achieved, and the membrane flux is very low.
[0048] In Example 3, by preparing amphoteric cyclodextrin, crystals were grown in situ on the surface of a porous support membrane to prepare a biligand metal organic framework membrane based on amphoteric cyclodextrin, such as Figure 1As shown in the figure, the membrane structure prepared by this method is uniform. By regulating the growth process of the crystal, controlling the size of the "nanochannel" between the crystal particles and the hydrophilicity of the channel, the transmission rate of water molecules in the membrane is increased, and a high water permeation flux is obtained; at the same time, the hydrophobic cavity of the amphiphilic cyclodextrin itself and the pore structure of the metal organic framework work synergistically to enhance the ion recognition function, so that the final membrane has high separation selectivity for heavy metal ions of different valence states. Therefore, the amphiphilic cyclodextrin dual ligand metal organic framework separation membrane has both high water permeability and excellent heavy metal ion separation selectivity.
[0049] Embodiment 4:
[0050] 3.0 g of α-cyclodextrin, 7 g of 2,6-diaminopyridine propane-1-sulfonic acid inner salt and 0.7 g of di(2-epoxypropyl) ether were dissolved in 100 g of 0.03 wt% potassium hydroxide aqueous solution, and reacted at 55° C. for 1.5 hours. After the reaction, the product was purified by water dissolution and methanol precipitation three times, and vacuum dried at 40° C. for 12 hours to obtain amphoteric cyclodextrin solid powder;
[0051] Take 0.2g of amphoteric α-cyclodextrin solid powder and 0.8g of zinc nitrate, add 100g of a mixed solvent of water and ethanol in a mass ratio of 5:1 to obtain a mixed solution, and coat the above mixed solution on the surface of a polyacrylonitrile ultrafiltration membrane at 15°C for 2 hours, and the amphoteric α-cyclodextrin metal coordination crystals are deposited on the surface of the polyacrylonitrile ultrafiltration membrane. Then, it is immersed in 0.1wt% 2-methylimidazole ethanol solution at 15°C for 2 hours to form an amphoteric cyclodextrin biligand metal organic framework primary eco-membrane, and then the above amphoteric cyclodextrin biligand metal organic framework primary eco-membrane is immersed in 0.1wt% terephthaloyl chloride n-hexane solution, cross-linked at 15°C for 10 minutes, and finally cured at 50°C for 25 minutes. After washing with deionized water, a separation membrane based on amphoteric cyclodextrin biligand metal organic framework is obtained.
[0052] The amphiphilic cyclodextrin dual ligand metal organic framework separation membrane has a good performance at 25℃ and 0.1MPa pressure for 1g·L -1 The filtration separation effect of heavy metal salt solution is: water flux is 100.0L·m -2 ·h -1 The retention rates of ferric chloride, chromic chloride, ferrous chloride and cupric chloride were 96.3%, 24.3%, 18.5% and 19.9%, respectively. The separation selectivities of ferric chloride / chromic chloride, ferric chloride / ferrous chloride and ferric chloride / cupric chloride were 20.5, 22.0 and 21.7, respectively.
[0053] Embodiment 5:
[0054] 4.5 g of γ-cyclodextrin, 9 g of 1,2-bis[N-methyl-N-(3-sulfopropyl)-alkylammonium]ethane and 1 g of ethylene glycol diglycidyl ether were dissolved in 100 g of a 0.6 wt% sodium hydroxide aqueous solution, and reacted at 50° C. for 4 hours. After the reaction, the product was purified by water dissolution and methanol precipitation three times, and vacuum dried at 40° C. for 12 hours to obtain amphoteric cyclodextrin solid powder;
[0055] Take 0.4g of amphoteric γ-cyclodextrin solid powder and 1.6g of zinc nitrate, add 100g of a mixed solvent of water and ethanol in a mass ratio of 5:3 to obtain a mixed solution, and coat the above mixed solution on the surface of a polyvinylidene fluoride ultrafiltration membrane at 25°C for 1.5 hours, and the amphoteric γ-cyclodextrin metal coordination crystals are deposited on the surface of the polyvinylidene fluoride ultrafiltration membrane. Then, it is immersed in 0.6wt% benzimidazole ethanol solution at 25°C for 1.5 hours to form an amphoteric cyclodextrin biligand metal organic framework primary eco-membrane, and then the above amphoteric cyclodextrin biligand metal organic framework primary eco-membrane is immersed in 0.25wt% of trimesaldehyde toluene solution, cross-linked at 25°C for 5 minutes, and finally cured at 65°C for 20 minutes. After washing with deionized water, a separation membrane based on amphoteric cyclodextrin biligand metal organic framework is obtained.
[0056] The amphiphilic cyclodextrin dual ligand metal organic framework separation membrane has a good performance at 25℃ and 0.1MPa pressure for 1g·L -1 The filtration separation effect of heavy metal salt solution is: water flux is 95.0L·m -2 ·h -1 The retention rates of ferric chloride, chromic chloride, ferrous chloride and cupric chloride were 96.4%, 25.2%, 19.8% and 20.6%, respectively. The separation selectivities of ferric chloride / chromic chloride, ferric chloride / ferrous chloride and ferric chloride / cupric chloride were 14.9, 16.1 and 15.9, respectively.
[0057] Embodiment 6:
[0058] 6 g of β-cyclodextrin, 7 g of 2,6-diaminopyridinepropane-1-carboxylic acid inner salt and 1.5 g of trimethylolpropane triglycidyl ether were dissolved in 100 g of 0.3 wt% potassium hydroxide aqueous solution, and reacted at 70° C. for 1 hour. After the reaction, the product was purified by water dissolution and methanol precipitation for 3 times, and vacuum dried at 40° C. for 12 hours to obtain amphoteric cyclodextrin solid powder;
[0059] Take 0.2g of amphoteric β-cyclodextrin solid powder and 0.2g of zinc nitrate, add 100g of a mixed solvent of water and ethanol in a mass ratio of 5:1 to obtain a mixed solution, and coat the above mixed solution on the surface of a polysulfone ultrafiltration membrane at 20°C for 3 hours, and deposit amphoteric γ-cyclodextrin metal coordination crystals on the surface of the polysulfone ultrafiltration membrane. Then, immerse it in 0.8wt% 2-methylimidazole methanol solution at 20°C for 3 hours to form an amphoteric cyclodextrin biligand metal organic framework primary eco-membrane, and then immerse the above amphoteric cyclodextrin biligand metal organic framework primary eco-membrane in 0.15wt% trialdehyde pyrogallol mesitylene solution, cross-link at 20°C for 8 minutes, and finally cure at 55°C for 25 minutes. After washing with deionized water, a separation membrane based on amphoteric cyclodextrin biligand metal organic framework is obtained.
[0060] The amphiphilic cyclodextrin dual ligand metal organic framework separation membrane has a good performance at 25℃ and 0.1MPa pressure for 1g·L -1 The filtration separation effect of heavy metal salt solution is: water flux is 103.0L·m -2 ·h -1 The retention rates of ferric chloride, chromic chloride, ferrous chloride and cupric chloride were 96.1%, 20.8%, 18.5% and 19.7%, respectively. The separation selectivities of ferric chloride / chromic chloride, ferric chloride / ferrous chloride and ferric chloride / cupric chloride were 20.3, 20.9 and 20.6, respectively.
[0061] Embodiment 7:
[0062] 4.4 g of α-cyclodextrin, 2.2 g of butanediol disuccinate dichlorohydroxypropyl quaternary ammonium diester sulfonate sodium and 1.2 g of epichlorohydrin were dissolved in 100 g of a 1 wt% potassium hydroxide aqueous solution, and reacted at 65° C. for 3 hours. After the reaction, the product was dissolved in water and purified by methanol precipitation 3 times, and vacuum dried at 40° C. for 12 hours to obtain amphoteric cyclodextrin solid powder;
[0063] Take 0.4g of amphoteric α-cyclodextrin solid powder and 1.6g of cobalt nitrate, add 100g of a mixed solvent of water and ethanol in a mass ratio of 5:4 to obtain a mixed solution, and coat the above mixed solution on the surface of a polyethersulfone ultrafiltration membrane at 15°C for 4 hours, and deposit amphoteric γ-cyclodextrin metal coordination crystals on the surface of the polyethersulfone ultrafiltration membrane. Then, soak it in 0.5wt% of trimesic acid ethanol solution at 15°C for 4 hours to form an amphoteric cyclodextrin biligand metal organic framework primary eco-membrane, and then soak the above amphoteric cyclodextrin biligand metal organic framework primary eco-membrane in 0.1wt% phthaloyl chloride cyclohexane solution, cross-link it at 15°C for 10 minutes, and finally cure it at 65°C for 15 minutes. After washing with deionized water, a separation membrane based on amphoteric cyclodextrin biligand metal organic framework is obtained.
[0064] The amphiphilic cyclodextrin dual ligand metal organic framework separation membrane has a good performance at 25℃ and 0.1MPa pressure for 1g·L -1 The filtration separation effect of heavy metal salt solution is: water flux is 109.0L·m -2 ·h -1 The retention rates of ferric chloride, chromic chloride, ferrous chloride and cupric chloride were 96.8%, 29.8%, 22.4% and 24.3%, respectively. The separation selectivities of ferric chloride / chromic chloride, ferric chloride / ferrous chloride and ferric chloride / cupric chloride were 21.9, 24.3 and 23.7, respectively.
[0065] Embodiment 8:
[0066] 2 g of γ-cyclodextrin, 5 g of 2,6-diaminopyridinepropane-1-carboxylic acid inner salt and 0.5 g of di(2-epoxypropyl)ether were dissolved in 100 g of 0.8 wt% sodium hydroxide aqueous solution, and reacted at 50° C. for 2.5 hours. After the reaction, the product was purified by water dissolution and methanol precipitation three times, and vacuum dried at 40° C. for 12 hours to obtain amphoteric cyclodextrin solid powder;
[0067] Take 0.3g of amphoteric γ-cyclodextrin solid powder and 2g of ferric chloride, add 100g of a mixed solvent of water and ethanol in a mass ratio of 5:2 to obtain a mixed solution, apply the above mixed solution on the surface of a polysulfone ultrafiltration membrane at 15°C for 3.5 hours, and deposit amphoteric γ-cyclodextrin metal coordination crystals on the surface of the polysulfone ultrafiltration membrane. Then, soak it in 0.2wt% of trimesic acid ethanol solution at 15°C for 3.5 hours to form an amphoteric cyclodextrin biligand metal organic framework primary eco-membrane, and then soak the above amphoteric cyclodextrin biligand metal organic framework primary eco-membrane in 0.3wt% trimesic acid chloride heptane solution, cross-link at 15°C for 10 minutes, and finally cure at 65°C for 30 minutes. After washing with deionized water, a separation membrane based on amphoteric cyclodextrin biligand metal organic framework is obtained.
[0068] The amphiphilic cyclodextrin dual ligand metal organic framework separation membrane has a good performance at 25℃ and 0.1MPa pressure for 1g·L -1 The filtration separation effect of heavy metal salt solution is: water flux is 92.0L·m -2 ·h -1 The retention rates of ferric chloride, chromic chloride, ferrous chloride and cupric chloride were 96.3%, 30.1%, 23.4% and 25.6%, respectively. The separation selectivities of ferric chloride / chromic chloride, ferric chloride / ferrous chloride and ferric chloride / cupric chloride were 18.9, 20.7 and 20.1, respectively.
Claims
1. A method for preparing a separation membrane based on an amphiphilic cyclodextrin dual ligand metal organic framework, characterized in that: The method comprises the following preparation steps: 1) dissolving 1.0 to 7.0 parts by weight of cyclodextrin, 2.5 to 12 parts by weight of zwitterionic amine monomers and 0.3 to 1.5 parts by weight of epoxy crosslinking agents in 100 parts by weight of alkaline aqueous solution, reacting at 50 to 70° C. for 1 to 4 hours, and after the reaction, purifying the product by dissolving and precipitating, and then heating and drying to obtain amphoteric cyclodextrin solid powder; 2) adding 0.1-0.5 parts by mass of the above-mentioned amphoteric cyclodextrin solid powder and 0.2-2 parts by mass of a metal acid salt to 100 parts by mass of a mixed solvent of water and ethanol to obtain a mixed solution, coating the above-mentioned mixed solution on the surface of a porous support membrane at 15-25° C. for 0.5-3 hours, depositing amphoteric cyclodextrin metal coordination crystals on the surface of the porous support membrane, and then impregnating with a second organic ligand solution with a mass percentage concentration of 0.1-1.0wt% to form a primary ecological membrane based on an amphoteric cyclodextrin dual ligand metal organic framework; 3) Immersing the above-mentioned amphiphilic cyclodextrin dual ligand metal organic framework based primary ecological membrane in a crosslinker solution with a mass percentage concentration of 0.05-0.3wt% for crosslinking, and finally subjecting it to thermal curing treatment at 40-65°C for 10-30 minutes, and washing with deionized water to obtain an amphiphilic cyclodextrin dual ligand metal organic framework membrane; The cyclodextrin is composed of one or more of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin in any proportion; the zwitterionic amine monomer is composed of one or more of N-aminoethylpiperazine propane-1-sulfonic acid inner salt, 2,6-diaminopyridine propane-1-sulfonic acid inner salt, 2,6-diaminopyridine propane-1-carboxylic acid inner salt, 1,2-bis[N-methyl-N-(3-sulfopropyl)-alkylammonium]ethane, and butanediol disuccinic acid dichlorohydroxypropyl quaternary ammonium diester sodium sulfonate in any proportion; the epoxy crosslinking agent is epichlorohydrin, di(2-epoxypropyl) ether, ethylene glycol diglycidyl ether, trimethylolpropane tris(2-hydroxypropyl) ether, and tris(2-hydroxypropyl) ether. One or more of the glycidyl ethers are mixed in any proportion; the metal acid salt is one or more of zinc acetate, zinc nitrate, ferric chloride, and cobalt nitrate mixed in any proportion; the porous support membrane is a polysulfone ultrafiltration membrane, a polyethersulfone ultrafiltration membrane, a polyacrylonitrile ultrafiltration membrane, or a polyvinylidene fluoride ultrafiltration membrane; the second organic ligand is one or more of benzimidazole, 2-methylimidazole, and trimesic acid mixed in any proportion; the cross-linking agent is one or more of phthaloyl chloride, terephthaloyl chloride, trimesic chloride, trimesic acid, terephthalaldehyde, trialdehyde-phloroglucinol, cyanuric chloride, and hexachlorotriphosphazene mixed in any proportion.
2. The preparation method according to claim 1, characterized in that The alkaline aqueous solution described in step 1) is a sodium hydroxide or potassium hydroxide aqueous solution with a mass percentage concentration of 0.01 to 1.0 wt%.
3. The preparation method according to claim 1, characterized in that: In step 1), the dissolution-precipitation purification method is to dissolve the product in water and precipitate it in methanol, and obtain the purified product after 3 to 6 dissolution-precipitation cycles.
4. The preparation method according to claim 1, characterized in that: The heating and drying conditions in step 1) are vacuum drying at 40 to 60° C. for 3 to 12 hours.
5. The preparation method according to claim 1, characterized in that: The mass ratio of water to ethanol in the mixed solvent described in step 2) is 5:1 to 5:
4.
6. The preparation method according to claim 1, characterized in that: The solvent of the second organic ligand solution in step 2) is water, methanol or ethanol.
7. The preparation method according to claim 1, characterized in that: The immersion treatment condition of the second organic ligand solution in step 2) is immersion at 15-25° C. for 0.5-4 hours.
8. The preparation method according to claim 1, characterized in that: The solvent of the cross-linking agent solution in step 3) is n-hexane, cyclohexane, heptane, toluene or mesitylene.
9. The preparation method according to claim 1, characterized in that: The cross-linking conditions in the cross-linking agent solution in step 3) are cross-linking at 15 to 25° C. for 2 to 10 minutes.
10. A separation membrane based on an amphiphilic cyclodextrin dual ligand metal organic framework prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Heavy metal ion adsorption film and preparation method thereof
CN112111078A
Preparation method of metal organic framework separation membrane through amphoteric particle in-situ construction
CN109550406A
Preparation method of ultra-low-pressure and high-flux metal-organic nano particle assembly nanofiltration membrane
CN109603555A